Healing of excisional wound in alloxan induced diabetic sheep: A planimetric and histopathologic study - Kazemi-Darabadi, Siamak (Vet Res Forum, 2013)
Healing of skin wound is a multi-factorial and complex process. Proper treatment of diabetic wounds is still a major clinical challenge. Although diabetes mellitus can occur in ruminants, healing of wounds in diabetic ruminants has not yet been investigated. The aim of this study was to evaluate healing of ovine excisional diabetic wound model. Eight 4-month-old Iranian Makoui wethers were equally divided to diabetic and nondiabetic groups. Alloxan monohydrate (60 mg kg(-1), IV) was used for diabetes induction. In each wether, an excisional wound was created on the dorsum of the animal. Photographs were taken in distinct times for planimetric evaluation. Wound samples were taken on day 21 post-wounding for histopathologic evaluations of epidermal thickness, number of fibroblasts and number of new blood vessels. The planimetric study showed slightly delay in wound closure of diabetic animals, however, it was not significantly different from nondiabetic wounds (p ≥ 0.05). Furthermore, epidermal thickness, number of fibroblasts and number of blood vessels were significantly lower in diabetic group (p < 0.05). We concluded that healing of excisional diabetic wounds in sheep may be compromised, as seen in other species. However, contraction rate of these wounds may not be delayed due to metabolic features of ruminants and these animals might go under surgeries without any serious concern. However, healing quality of these wounds may be lower than normal wounds.